2019
DOI: 10.1080/10715762.2019.1618851
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity and health benefits of anthocyanin-rich fruit juice in healthy volunteers

Abstract: Oxidative cell damage has been linked to the pathogenesis of numerous diseases such as atherosclerosis, type 2 diabetes, and cancer. The consumption of foods rich in polyphenols (e.g. anthocyanins) has been shown to exert preventive effects against such diseases. We investigated the biological effects of anthocyanin-rich fruit juice in a 9-week, placebo-controlled intervention study with 57 healthy male volunteers. The study design encompassed an initial 1 week of wash-out, followed by 8 weeks of intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 39 publications
3
66
0
2
Order By: Relevance
“…Furthermore, the DNA integrity was affected by the anthocyanin-rich beverages. Taken together, the applied red fruit juice blend (beverage 1) showed the most promising properties for further studies on long-term effects of a consumer-relevant anthocyanin-rich juice, as recently shown by Bakuradze et al [25].…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, the DNA integrity was affected by the anthocyanin-rich beverages. Taken together, the applied red fruit juice blend (beverage 1) showed the most promising properties for further studies on long-term effects of a consumer-relevant anthocyanin-rich juice, as recently shown by Bakuradze et al [25].…”
Section: Resultssupporting
confidence: 54%
“…The consumption of deeply pigmented foods rich in polyphenolic anthocyanins (ACNs), with marked antioxidant and anti-inflammatory activity, has been shown to exert preventive effects against chronic diseases. In a placebo-controlled intervention (n=57), ACN-rich juice consumption for 9 weeks caused DNA protective and antioxidant effects, which were also observed unexpectedly in the placebo group (15). The authors of that study proposed that vitamin C was responsible for the placebo effect.…”
Section: Discussionmentioning
confidence: 97%
“…and obese subjects: A randomized, crossover pilot study of less nutritious, calorie-dense beverages, such as soft drinks (12,13). Moreover, numerous fruit juices are produced from exotic 'superfruits', such as noni, maqui, acai, goji, pomegranate, etc., due to their complement of beneficial bioactive, e.g., antioxidant, compounds, which can lead to robust health benefits (14,15). However, there is limited published information available on the toxicity profiles of some dietary fruit juices due to their prevalence in the food supply, common use and the general lack of evidence that would support safety concerns.…”
Section: Tart Cherry Juice Consumed Daily For 4 Weeks Does Not Impairmentioning
confidence: 99%
“…Besides the ACs, the abovementioned fruits also contain so-called copigments-colorless phenolic compounds such as phenolic acids, flavonols, and proanthocyanidins that can stabilize the colored structural form of the ACs and enhance their color intensity through intermolecular interactions or shifts in maximum absorption [4]. Several studies showed that ACs and copigments possess antioxidant, anti-inflammatory, and antidiabetic properties and are associated with numerous health benefits [6][7][8][9][10][11][12]. Reports also suggest that lipolytic activity can be influenced by polyphenols such as flavonoids and flavanones via inhibition of 3 ,5 -cyclic adenosine monophosphate (cAMP)-phosphodiesterase, as demonstrated by an increasing cAMP level [13,14].…”
Section: Introductionmentioning
confidence: 99%